KEHADIRAN KOMISARIS INDEPENDEN PADA HUBUNGAN KOMPENSASI EKSEKUTIF DENGAN KECURANGAN LAPORAN KEUANGAN - Indiraswari, Susmita Dian; Izzalqurny, Tomy Rizky (Fakultas Ekonomi, Program Studi Akuntansi, 2021)
This study aims to analyze the effect of compensation on fraud in financial statements moderated by independent commissioners. This study uses quantitative methods using multiple regression analysis techniques. This research was conducted with manufacturing companies on the Indonesia Stock Exchange (IDX) from 2017 to 2019, this study used purposive sampling so that 223 firm years were obtained. The results of this study are executive compensation has a negative effect on financial statement fraud. Independent commissioners who are tasked with implementing and implementing the company's good corporate governance system standards properly and correctly, it turns out that in this study it was not proven to moderate the relationship between financial statement fraud and compensation obtained from the board of directors, but the presence of independent commissioners will reduce the level of financial statement fraud.Keywords: financial statement fraud; compensation; independent commissioner; GCG.